Pengaruh PAD, Belanja Modal, Ukuran Pemerintah, dan Perubahan Anggaran Terhadap Kinerja Keuangan Daerah (Di Provinsi Jawa Tengah Tahun 2019-2021) - Bunga Widya Safitri; Novi Dirgantari; Eko Hariyanto; Dwi Winarni (Politeknik Bisnis Indonesia, 2022)
The pandemic due to Covid19 has had an impact on district/city regional government budget policies in Central Java which has resulted in a decrease in regional financial performance. The purpose of this study is to examine the effect of Regional Original Income, Capital Expenditure, Government Size, and Budget Changes on the Regional Financial Performance of Regencies and Cities in Central Java Province in 2019-2021. The sampling technique used was a saturated sample, so that 35 district and city governments in Central Java were obtained. The research method used is Quantitative. The analysis technique uses multiple regression analysis. The results of the study show that the Regional Original Income Variable and Government Size have a positive effect on regional financial performance while the Capital Expenditure Variable and Budget Changes have a negative effect on regional financial performance.